Enhancing the ESP Lesson with IMMERSE: a Pedagogical Example of a Metaverse Language Learning Platform - Christoforou, Maria (My University, 2022)
Virtual Reality (VR) is becoming significantly prevalent in the field of education and has been proven, among others, to increase student motivation and commitment to the lesson, to simulate contextualized scenarios for learning and to help students practice their public speaking skills. This innovative technology has provided unprecedented opportunities for student interaction with the lesson content which is achieved through the multisensory experience it offers and the replacement of interaction with immersion. In fact, some VR-related impediments, such as the high cost of the hardware (for tethered headsets), the set-up of the computer hardware and correct connection of the Head Mount Display (HMD), are gradually being overcome due to the emergence of more commercially accessible VR standalone headsets (in price and ease of equipment use), like Oculus Quest 2. However, even though the number of VR applications has been exponentially increasing, most of these applications are not designed to support teaching practices and they lack pedagogical foundation. The field of English for Specific Purposes (ESP) is a field which can benefit from VR since the latter can provide ESP learners with virtual trips to professional contexts, it can increase their experiential element and simulate authentic conditions, and it can also help with vocabulary retention. This paper aims to theoretically propose ways that IMMERSE, an educational metaverse language learning platform, can enhance the learning experience of ESP students. Specifically, it is believed that the affordances of the platform (various real-life contexts, high levels of immersion and interactivity) as well as its fundamental elements of language immersion practice (functional language, culture, and community building) can enhance the ESP lesson and provide more contextualized opportunities for students to practice the language.
Keywords: IMMERSE; English for Specific Purposes (ESP); Immersive Learning; Virtual Reality-assisted language learning (VRALL)